Immunohistochemical study of the endocrine cells in the oesophagus of the ostrich (Struthio camelus) - Yaman, M.; Gençer Tarakçi, B.; Bayrakdar, A.; Yaman, I. (My University, 2008)
The presence of serotonin, substance P, calcitonin gene related peptide (CGRP), somatostatin-14, neurotensin, cholecystokinin (CCK), galanin and vaso-active intestinal polypeptide (VIP) endocrine cells in the oesophagus of the ostrich (Struthio camelas) was investigated by immunohistochemistry. CCK, substance P and galanin immunoreactive endocrine cells were observed in oesophagus of ostrich with high, intermediate and low frequencies respectively. However, no endocrine cells showing immunoreactivity for serotonin, CGRP, somatostatin, neurotensin and VIP was evidenced. These results suggest that the distribution pattern of endocrine cells in the digestive apparatus of specific not only of the avian specie but also of the considered part of the digestive tract.
Keywords: CGRP; Cholecystokinin; Endocrine cells; Immunohistochemistry; Neurotensin; Oesophagus; Ostrich; Somatostatin; Substance P; VIP